Growth impacts of Swiss steering-based climate policies - Adriana Marcucci; Lin Zhang (Swiss Journal of Economics and Statistics, 2019)
This paper studies the growth impacts of realizing two long-term carbon targets in Switzerland (reducing CO2 emissions in 2050 by 72% and 80% relative to 1990 levels) with alternative steering-based climate policies that include a uniform tax on the whole economy and differentiated tax schemes. For this analysis, we use the Computable Induced Technical change and Energy (CITE) model, a computable general equilibrium (CGE) model with endogenous growth. We find that achieving the climate targets could lead to a slight decrease in utility and an increase in investments through the shift of labor from manufacturing to research. Higher investments coming from higher innovation could compensate the reduction in output due to the carbon policies, leading to relatively unaffected economic output. The economic structure adjusts following three drivers: energy intensity, substitutability from energy in the production of the intermediate varieties, and the relative attractiveness of research. Moreover, the results from the CITE model show that the economy-wide carbon tax is the most effective option when we consider the effects on utility. Differentiating the sectors regulated by the emission trading system (ETS) has relatively low impact while applying lower taxes on transport fuels results in lower utility driven by inefficiencies in the sectoral mitigation efforts. Finally, we find that the effects of increasing the stringency of the target (in terms of foregone utility) are independent from the policy instrument.
Keywords: 330; Endogenous growth; Swiss climate policy; CGE; Differentiated taxes